Triboelectric nanogenerators as flexible power sources. (December 2017) - Wang, Yang; Yang, Ya; Wang, Zhong
Abstract The triboelectric nanogenerator (TENG) as a new power-generation technology was reported by Wang and co-workers in 2012. Because of its great potential for scavenging mechanical energy from living environment and sustainably driving portable devices, many researchers have developed various methods to improve output performances of TENG. In this paper, we review the progress in TENG made as flexible power sources by integrating flexible materials and stretching structures, especially for the applications of flexible electronics. For optimizing performances of TENG, the structural designs, material selections, and hybrid energy cells are presented. The reported TENG as flexible power sources has the potential applications in lighting up light emitting diodes (LEDs), powering sensors, and monitoring biomechanical motions.